Improving inclusion of students with disabilities in Malaysian higher education - Yusof, Yusmarhaini; Chan, Cheong Chong; Hillaluddin, Azlin Hilma; Ahmad Ramli, Fatimah Zailly; Mat Saad, Zarina (Routledge, 2020)
Malaysia aims to increase the participation of students with disabilities in Higher Education. This study examines the experiences of students with disabilities in selected Malaysian universities. Interviews with 14 students and 5 administrators indicated that universities need to play more active roles to eliminate barriers to access and participation. Participants’ accounts showed that the central role of universities lies in providing services, access, organising logistics, creating awareness, ensuring disabled-friendly facilities and developing specific policies to address issues concerning disabilities. Suggestions included increasing funding allocations, having Offices of Disability, and incorporating Universal Design (UD) and Universal Design for Learning (UDL) to increase participation.